Handling bandar baru Setiawan P\Perdana site progress work, valuation on site and preparation of interim payment certificate / Shazieta Adlika Ahmad Zaki - Ahmad Zaki, Shazieta Adlika (Universiti Teknologi Mara, Perak, 2018)
Handling site progress work and preparation of interim payment certificate for contractor progress work claims for a project generally needs a distinctive scrutiny which require the exact valuation of progress work for contractors which lead to correct amount of payment for the payment certificate. The execution of valuation on site works for the progress by the contractor require full attention to ensure that the work executed by the contractor and the progress they submitted are parallel. If any unclear or different amount of valuation that made, the contractor needs to re-submit the new progress work for claiming progress work. The preparation of the Interim Payment Certificate for the contractor require the deep understanding on the value that are going to be inserted. Any wrong amount inserted may affect the other amount executed before. Therefore the objective of this report execution is to study clearly about the site progress work valuation method and the payment for contractor for the project implemented for handling the development of Bandar Baru Setia Awan Perdana (BBSAP). The direct involvement for the handling of the site progress claims and valuation on site of progress work by the contractor has exposed the student on method used for valuation has expand and provide the wide range of knowledge for the contract and construction management subject.